'One-in, one-out' in the European Union legal system: a deceptive reform? - Éric Van den Abeele (European Trade Union Institute (ETUI), 2020)
Since 2002 and the publication of the Mandelkern report,1 the question of reducing burdens and costs, both regulatory and administrative, has emerged as a recurrent topic that regularly comes up at the European Council. It is, moreover, revealing that one of the points of rupture that led the United Kingdom to opt for Brexit2 was the issue of 'better lawmaking'.3 In this context, the system of regulatory compensation 'one-in, one-out' - which involves setting off against every new cost arising from a legislative initiative the elimination of an existing cost - has become a potent political symbol, if the warm welcome afforded it by a dozen member states and, in particular, the European employers' lobby Business Europe is anything to go by. Some have gone so far as to attribute veritable healing powers to 'one-in, one-out', such as reducing the unduly onerous costs of the European bureaucratic machinery for businesses. By showcasing this accounting-based approach, which lacks precise economic substance, the sponsors of 'one-in, one-out' believe that they have found a kind of automatic brake that will help them to strip the acquis communautaire of some of its obligations and 'unnecessary' costs. Claims of significant savings have been made, sometimes recklessly, as if a new Eldorado was on the horizon for businesses. Germany, which will take over the presidency of the European Council for six months from 1 July 2020, tasked a team of researchers at the Centre for European Policy Studies (CEPS) with drafting a report4 on the feasibility of introducing this approach at the level of the European Commission. The presentation of this report and its critical analysis are the topic of the present publication. It is important to note that this debate is coming in the wake of the Von der Leyen Commission's approval, in December 2019, of an ambitious roadmap of more than 50 measures on a Green Deal for Europe, both legislative and nonlegislative. While the European Union (EU) needs rules to provide it with legal certainty and predictability, as well as a level playing field with its trade partners, the notion that law impedes smooth business operations is making a comeback. The issue of regulatory compensation, in the form of 'one-in, one-out', will be high on the agenda of Angela Merkel's government during Germany's EU presidency. The first Council Conclusions on the topic have already been adopted, at the ministerial session of 27 February 2020. This debate is important because it will determine the EU's role in the coming years.
Keywords: 330; EU law; compensation measure; compliance costs; EU countries; EU-Recht; Kompensationsmaßnahme; Befolgungskosten; EU-Staaten